Review of Diane Ravitch's Book, "The Life and Death of American Public Schools,” - Angela Affronti (Networks: An Online Journal for Teacher Research, 2012)
“And who are you and why are you here?” asked a student my first day of my practicum at a public middle school in lower Manhattan. “I am here from NYU to help you with your reading,” I responded with a friendly smile. Looking back at this exchange, I realized that not only did I work hard to help and gain acceptance from the students, I was working just as hard to learn more about public school structures, specifically since I was in NY, the bureaucratic structure that is the NYC Board of Education. While I was working in the schools, I began to open my eyes wider and dig deeper to see what really was occurring in the schools. Diane Ravitch, a historian of education and also an NYU professor does the same in her book, “The Life and Death of American Public Schools.” I was lucky enough to hear her speak at the 2011 National Council for the Social Studies Conference in Washington D.C. Her speech discussed various educational reforms and displayed statistics reporting how schools are doing before and after the reforms. Ravitch concluded that the same reforms that were intended to make public education better are in fact making it worse.